A new genus of the tribe Parahiraciini (Hemiptera: Fulgoroidea: Issidae) from Southern China - Wang, Menglin; Bourgoin, Thierry; Zhang, Yalin (Zootaxa, 2015)
A new genus Tetricodissus gen. nov. with one new species Tetricodissus pandlineus sp. nov. from Yunnan Province, China, is described and illustrated in the tribe Parahiraciini of planthopper family Issidae. Fortunia jianfenglingensis Chen, Zhang & Chang, 2014 is transferred into the genus Bardunia Stål, 1863. A key to genera of the tribe Parahiraciini is provided and the taxonomic position of the new genus in Parahiraciini is discussed.